Effects of Service Quality, Food Quality, and Price Fairness Customer Satisfaction at Japanese restaurant 3 Wise Monkeys, Jakarta - Rara Wilis Setiawati; Innocentius Bernarto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of  this study was to analyze the  positive influence of service  quality, price fairness, and food quality positive effects on customer satisfaction.   The target population of the study is all customers of Japanese restaurant 3 Wise Monkeys Jakarta.  As for determining the sample using  purposive sampling techniques. The specified sample number is 200 samples that are customers of  Japanese restaurant  3 Wise Monkeys.  The data is collected by distributing questionnaires. The data was analyzed using the partial least square-structural equation modeling (PLS-SEM) model.  The results showed that service  quality, price fairness, and food quality had  a positive influence on  customer satisfaction at  Japanese restaurant 3 Wise Monkeys.